The Reality of Strategic Agility and its Impact on Achieving Organizational Excellence at Taif University - Al-Jaeed, Samia Ayed (The Arab Journal of Administration, 2025)
The study aims to identify the reality of strategic agility and its impact on organizational excellence at Taif University. It also aims to determine the degree of practice of strategic agility at Taif University from the point of view of academic leaders, and to determine the degree of practice of organizational excellence at Taif University from the point of view of academic leaders, and to ensure that there is A correlation between strategic agility and organizational excellence from the point of view of academic leaders, and ensuring that there are statistically significant differences between the average response of sample members in the degree of practicing strategic agility due to demographic variables (gender, academic rank, years of experience), and ensuring that there are significant differences Statistics between the average response of the sample members in the degree of organizational excellence practitioner are attributed to demographic variables (gender, academic rank, years of experience). To achieve the objectives of the study, the researcher followed the descriptive, correlational approach represented by using regression analysis to measure the effect of the independent variable (strategic agility) on the dependent variable (Organizational excellence), due to its suitability for the purposes of the study. The research community consisted of all academic leaders at Taif University during the second semester of the year (1444 AH), and the survey form was relied upon as a data collection tool. After applying the study, the following results were concluded: There is an impact of applying the dimensions of strategic agility on achieving organizational excellence. The study recommends the effective application of the dimensions of strategic agility due to its positive impact on organizational excellence and its dimensions and making it a priority for organizational work in universities..